Sujeito adulto universitário : qual o papel das emoções no processo de aprendizagem? - Baseggio, Denice Bortolin (2011)
This study is about the research in Educative Processes and Language for the Post Graduation Program in Education from Universidade de Passo Fundo/RS. In the review University Adult Individual: the emotions role in the learning process , the article discusses the features that characterize the university adult individual, the university context and the role of emotions in learning. The research used the qualitative approach, through the references provided by studies of narratives presented by Larrosa (2002), among others.Together with the psychoanalytic method, the narratives are constructed to give meaning to human experience and organize it in time. The narrate act allows the individual to interpret his life and to create a personal meaning to the events experienced, providing a place for himself in this world. The corpus of the research consisted of narratives produced by the teacher and the researcher and analyzed based on psychoanalytic theory, whose authors, among others, include: Freud, Winnicott, Bolwby, Bleichamar. It was analyzed three situations that revealed aspects of the learning difficulty that adults had, despite being able to develop their full physical and emotional capabilities. Through the three categories analyzed - identification, transfer and investment - it was found that the adult characterization differs from the literature presented in this research because the university context undergoes significant changes, particularly the technology, the easier access and the greater demand. The students indicate a reserved desire to invest in their formative professional process justifying this attitude by financial, family and emotional difficulties present in their contemporary life. It becomes, among other things, in a restricted investment in the learning process and the relationship with the teacher. It concludes, therefore, that emotion is an extremely important factor in the incidence of difficulties in the learning process of university adult individual